PENGGUNAAN GADGET TERHADAP PERILAKU SOSIAL ANAK DI SEKOLAH DASAR - Teguh Prasetyo (Jurnal Penjaminan Mutu, 2022)
The use of gadgets that are used effectively will have positive impacts on users. However, elementary school-age students have not been able to use gadgets effectively, so it is not uncommon for the use of gadgets to have more negative impacts than positive impacts. One of the negative impacts that are shown directly is the excessive use of gadgets that can affect students' social behavior. This study aims to analyze the impact of using gadgets on the social behavior of fifth-grade students at Elementary School 2 Tangkil, Cidahu District in Sukabumi Regency. This research uses a qualitative approach to the case study method. A qualitative approach so that researchers can reveal the impact of using gadgets on the social behavior of elementary school-age children. The research subjects consisted of nine students who already had their gadgets. The results showed that the use of gadgets in fifth-grade students at Elementary School 2 Tangkil for an average of three hours every day with a fairly high category. The positive impacts of using this gadget include gaining broad knowledge by searching for information on google, making it easier to communicate with others, and playing games that sharpen children's brains. Furthermore, students mentioned that gadget access activities were carried out for various information through google and searching for the subject matter, and helping with school assignments. In the aspect of social behavior, fifth-grade students at Elementary School 2 Tangkil are to be good criteria. Students can still show mutual help, courtesy, and respectness during the widespread use of gadgets in elementary school-aged children